Existing operational standards for field deployments of rapid response mobile laboratories: a scoping review - Mushasha, Rand; Paez Jimenez, Adela; Dolmazon, Virginie; Baumann, Jan; Jansen, Andreas; Storozhenko, Oleg Nikolayevich; El-Bcheraoui, Charbel (Frontiers in Public Health, 2024)
IntroductionRapid response mobile laboratories (RRML) play an important role in responding to emergencies such as outbreaks and humanitarian crises, working in coordination with national authorities. This scoping review aims to provide evidence to support the development of minimum operational standards for the deployment of RRMLs across the five key workstreams: operational support and logistics, biosafety and biosecurity, laboratory information management system, quality management systems and interoperability and coordination.MethodsWe searched PubMed, MEDLINE, EMBASE and the grey literature focusing on RRML deployment missions. Study characteristics such as year, country, objectives, methods, and findings were extracted and summarized to identify common themes, gaps, and patterns. The results were presented in a narrative format. We ensured methodological rigor by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines throughout the review process.ResultsOut of 163 full-text studies assessed for eligibility, 46 met the inclusion criteria and were analyzed. Six studies addressed the five RRML workstreams. Operational support and logistics are most commonly addressed during pre-deployment phases with a focus on personnel, transport and cold chain management. The application of biosafety and biosecurity protocols is most addressed during the mission execution phase, particularly in the use of personal protective equipment and the implementation of decontamination and disinfection procedures. The laboratory information management system procedures most frequently reported include sample identification and result dissemination protocols. The quality management system workstream overlaps significantly with the other four workstreams, with a strong emphasis on internal and external quality assurance measures. Coordination and interoperability aspects involve maintaining multiple collaborations, ranging from coordinating with local authorities to establishing international partnerships. Common field challenges included interrupted data transfer in areas characterized by poor connectivity and difficulties caused by extreme weather conditions.DiscussionThis review highlights RRML deployment procedures and addresses some critical challenges concerning their deployment. It suggests the provision of a pre-deployment logistics checklist, the use of a pre-determined standardized dataset for inputs to reduce data entry errors and the application of standardized internal and external quality assurance measures.